New method for generating deletions and gene replacements in Escherichia coli. - Hamilton, C M (1989)
We describe a method for generating gene replacements and deletions in Escherichia coli. The technique is simple and rapid and can be applied to most genes, even those that are essential. What makes this method unique and particularly effective is the use of a temperature-sensitive pSC101 replicon to facilitate the gene replacement. The method proceeds by homologous recombination between a gene on the chromosome and homologous sequences carried on a plasmid temperature sensitive for DNA replication. Thus, after transformation of the plasmid into an appropriate host, it is possible to select for integration of the plasmid into the chromosome at 44 degrees C. Subsequent growth of these cointegrates at 30 degrees C leads to a second recombination event, resulting in their resolution. Depending on where the second recombination event takes place, the chromosome will either have undergone a gene replacement or retain the original copy of the gene. The procedure can also be used to effect the transfer of an allele from a plasmid to the chromosome or to rescue a chromosomal allele onto a plasmid. Since the resolved plasmid can be maintained by selection, this technique can be used to generate deletions of essential genes.